Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ehj.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and short term effects of percutaneous atrial septal defect device closure on cardiac electrical remodeling in children

Abstract: BackgroundThe beneficial effects of atrial septal defect (ASD) device closure on electrical cardiac remodeling are well established. The timing at which these effects starts to take place has yet to be determined.ObjectivesTo determine the immediate and short term effects of ASD device closure on cardiac electric remodeling in children.Methods30 pediatric patients were subjected to 12 lead Electrocardiogram immediately before ASD device closure, 24 h post procedure, 1 and 6 months after. The maximum and minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…They found that mean P wave dispersion decreased after closure and this decrease continued even months after. 36 Grignani et al had similar results in their study and saw that 25 children with atrial septal defect whose defects were closed by transcatheter method had a decrease in P wave dispersion after 2 months of closure (p < 0.001). 37 On the other hand, there are studies claiming that there is no change in mean P wave dispersion after closure or moreover showing an increase after closure.…”
Section: Discussionmentioning
confidence: 61%
“…They found that mean P wave dispersion decreased after closure and this decrease continued even months after. 36 Grignani et al had similar results in their study and saw that 25 children with atrial septal defect whose defects were closed by transcatheter method had a decrease in P wave dispersion after 2 months of closure (p < 0.001). 37 On the other hand, there are studies claiming that there is no change in mean P wave dispersion after closure or moreover showing an increase after closure.…”
Section: Discussionmentioning
confidence: 61%
“…Ozylimaz et al [32] did not show any statistically significant change in P wave maximum duration and P wave dispersion at 24 h after percutaneous closure in a pediatric population. Conversely, Roushdy et al [15] describes a positive electrical remodeling, in terms of reduction of P wave and QTc dispersion, at 24 h from ASD closure with the Amplatzer device, and these changes were confirmed at 6 months. However, no data concerning the P wave dispersion were reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A greater dispersion of the QTc is an important electrophysiological marker that is directly related to greater susceptibility to ventricular arrhythmias and, no less, to sudden cardiac death in cases of several comorbidities [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation